Evaluating the pathways from small-scale irrigation to dietary diversity: evidence from Ethiopia and Tanzania - Passarelli, Simone; Mekonnen, Dawit Kelemework; Bryan, Elizabeth; Ringler, Claudia (Springer, 2018)
Interventions that aim to increase water availability for agriculture hold great potential for improving nutrition through increasing food production, generating income, enhancing water access and sanitation and hygiene conditions, and through strengthening women’s empowerment. Yet there is scarce evidence on the linkages between small-scale irrigation and the pathways through which nutrition outcomes can be achieved. Using data from a cross-sectional household survey collected in Ethiopia and Tanzania, we explored the potential for small-scale irrigation to contribute to improved diets, and identify the pathways through which irrigation affects dietary diversity as measured by the Household Dietary Diversity Score. Unadjusted comparisons show that irrigating households in both countries produced more vegetables, fruits and cash crops, are less food insecure, have a higher value of production, and have higher production diversity and dietary diversity compared to non-irrigating households. Econometric results of a simultaneous equation (3SLS) model showed that irrigation leads to better household dietary diversity mainly through the pathway of increasing household incomes. However, these results are statistically significant only in the case of Ethiopia, and not in Tanzania. While irrigation increased production diversity in Ethiopia, the benefits of increased dietary diversity cannot be attributed to these changes in production after controlling for the effect of income. Other factors, such as gender of the household head and having off-farm income, also influence dietary diversity in Ethiopia. These findings suggest that the potential for irrigation to influence diets is highly context-specific. Understanding the particular pathways and entry points for nutrition-sensitive agriculture approaches could help to improve their benefits for nutrition.